2019
DOI: 10.1088/1361-6463/ab4e6b
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependent structural evolution and crystallization properties of thin Ge15Te85 film revealed by in situ resistance, x-ray diffraction and scanning electron microscopic studies

Abstract: Chalcogenide-based Ge15Te85 thin films have recently been explored for ovonic threshold switching (OTS) selector devices for vertically stackable cross-point memory applications. Despite reasonable understanding over its crystallization kinetics and threshold switching properties, the structural stability and morphological acquaintance at elevated temperatures remain key challenges. In this paper, we investigate the thermal stability, surface morphology and local structure of as-deposited amorphous Ge15Te85 th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Hence, the two crystallization events in Figure 2 could be related to the crystallization of these two crystalline phases. Support for this hypothesis is found in the study by Sengottaiyan et al [31] and others, where tellurium was found to crystallize first. This is confirmed by the XRD data shown in Figure 3.…”
mentioning
confidence: 68%
“…Hence, the two crystallization events in Figure 2 could be related to the crystallization of these two crystalline phases. Support for this hypothesis is found in the study by Sengottaiyan et al [31] and others, where tellurium was found to crystallize first. This is confirmed by the XRD data shown in Figure 3.…”
mentioning
confidence: 68%
“…The issue in XRD determination of the crystallization threshold is that the method requires a sufficient volume of crystalline material for detection. There are examples of transmission electron microscope (TEM) images which show crystallites in otherwise amorphous films below the crystallization threshold determined in the same study by XRD (Sengottaiyan et al 2019). A small population of crystallites may therefore be present in all mirrors (Glover et al 2018).…”
Section: Introductionmentioning
confidence: 63%
“…The crystallization of Ge 15 Te 85 consists of two separate processes. The first crystallization process can be attributed to the crystallization of the Te constituent [104]. When the Te crystallizes, the remaining amorphous phase changes its composition towards that of GeTe.…”
Section: The Glass Transition Of Pcmsmentioning
confidence: 99%